Rethinking Autonomous and Robotic Systems in Residential Architecture - Sotirios Kotsopoulos; Jason Nawyn (Footprint)
Informed by twenty years of hands-on experimentation with autonomous and robotic systems in home prototypes at the Massachusetts Institute of Technology, this study provides insight into the motivations and values of integrating computing technologies in residential architecture. Although optimising home adaptability for energy efficiency, ergonomics, and climate control are shown to have benefits, applications intended to influence human behaviour remain questionable. The features of three home prototypes are presented to supply evidence for this claim: a Connected Sustainable Home that is a prototype of connected sustainability; the PlaceLab, a living laboratory for studying health-related home systems; and the CityHome, a series of robotically-transformable apartment prototypes. The case studies are of distinct scales, aim at heterogeneous objectives, and were implemented at different times. They are thematically linked through digital home automation. Evaluating these three prototypes enables the determination of design criteria for integrating autonomous and robotic systems in residential architecture and provokes reflection on the impact of autonomous systems on architectural practice.